SAT0437 Ixekizumab improves nail and skin lesions in patients with active psoriatic arthritis and prior tnf inadequate response. (15th June 2017) - Kristensen, LE; Merola, JF; Dutz, J; Adams, DH; Kerr, L; Rich, P
Abstract : Background: Ixekizumab (IXE), a high-affinity monoclonal antibody selectively targeting interleukin-17A, significantly improved fingernail psoriasis by Week (Wk) 12 vs placebo (PBO) in patients (pts) with moderate-to-severe plaque psoriasis 1 . Moreover, IXE had significantly reduced signs and symptoms of psoriatic arthritis (PsA) at Wk 24 in biologic disease-modifying antirheumatic drug (bDMARD)-naïve pts with active PsA 2 . Objectives: To evaluate the impact of IXE on nail and skin lesions in active PsA pts who have previously received bDMARD therapy. Methods: In this phase 3, multicentre, double-blind, PBO-controlled, outpatient study, pts (aged ≥18 years) with active PsA and bDMARD-experience randomly (1:1:1) received PBO for 24 Wks, 80 mg IXE as one injection every 2 (IXE Q2W) or 4 Wks (IXE Q4W) after starting dose of 160 mg. At Wk 16, inadequate responders received rescue medication and PBO pts were re-randomised (1:1) to receive either IXE Q2W or IXE Q4W. The efficacy of IXE was assessed by Nail Psoriasis Severity Index (NAPSI) in pts with nail psoriasis at baseline (PBO, n=73; IXE Q4W, n=89; IXE Q2W, n=74), Psoriasis Area and Severity Index (PASI) 75/90/100 response rate at Wk24 in pts with baseline body surface area (BSA) ≥3 (PBO, n=67; IXE Q4W, n=68; IXE Q2W, n=68) and percentage of pts achieving static Physician Global Assessment (sPGA) of psoriasis score of 0 (cleared) or 1 (minimal) in pts with baseline sPGA≥3 (PBO, n=55; IXEQ4W, n=60; IXEQ2W, n=62). Missing data and inadequate responder data were imputed using the nonresponder imputation for categorical variables. For continuous variables, least squares mean (LSM) changes were calculated using mixed effects models for repeated measures, observed data from Wks 16 to 24 was excluded for inadequate responders. Results: Overall the demographics and baseline characteristics were comparable between the treatment groups. The mean (SD) NAPSI total score at baseline was 19 (19), 20 (20), and 21 (22) in PBO, IXE Q4W and IXE Q2W, respectively. At Wk 24, the change in NAPSI total score from baseline was significantly greater with IXE Q4W (LSM±SE -10.2±2.04) and IXE Q2W (-10.8±2.12) vs PBO (0.5±2.13, p<.001 each). Similarly, the mean percentage improvement in NAPSI total score was significantly greater with IXE Q4W (LSM±SE 35.4±22.14, p<.001) and IXE Q2W (30.9±22.95, p=.001) vs PBO (-45.2±23.04). At Wk 24, significantly greater percentage of pts achieved a NAPSI score of 0 with IXEQ4W or IXEQ2W treatment vs PBO (Table). At Wk 24, the percentage of pts achieving PASI 75/90/100 response was significantly greater with IXE Q4W and IXE Q2W vs PBO (Table). Overall, the safety profile of IXE was aligned with the general study population. Conclusions: In the present study, ixekizumab led to significantly greater reduction and clearance of the nail and skin lesions in active PsA pts who had previously received bDMARD therapy compared to placebo. References: Dennehy EB et al. J Drugs Dermatol. 201615(8):958–61. Mease PJ, et al. Ann Rheum Dis. 2016 doi: 10.1136/annrheumdis-2016–209709. Disclosure of Interest: L. Kristensen Grant/research support from: UCB, Janssen-Cilag and Biogen, Consultant for: Pfizer, AbbVie, Amgen, UCB, Celegene, BMS, MSD, Novartis, Eli Lilly, and Janssen pharmaceuticals, Speakers bureau: Pfizer, AbbVie, Amgen, Biogen, UCB, Celegene, BMS, MSD, Novartis, Eli Lilly, and Janssen pharmaceuticals, J. Merola Grant/research support from: Biogen IDEC, Consultant for: Biogen IDEC, Amgen, AbbVie, and Eli Lilly, Novartis, Pfizer, Janssen, UCB, Kiniksa, Momenta and Mallinckrodt, J. Dutz Grant/research support from: Abbvie, Novartis, Amgen, Consultant for: Cipher, Speakers bureau: Janssen, Abbvie, Novartis, Amgen, Leo, Celgene, D. Adams Employee of: Eli Lilly and Company, L. Kerr Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Rich Grant/research support from: UCB, Janssen-Cilag and Biogen, Consultant for: Pfizer, AbbVie, Amgen, UCB, Celegene, BMS, MSD, Novartis, Eli Lilly, and Janssen pharmaceuticals, Speakers bureau: Pfizer, AbbVie, Amgen, Biogen, UCB, Celegene, BMS, MSD, Novartis, Eli Lilly, and Janssen pharmaceuticals.